Internalizing Morals and the Active Intervention of a Moral System: Zhu Xi and Yi Hwang’s Theories of kyŏngmul 格物 and mulgyŏk 物格 - Hyoungchan, Kim (Journal of Korean religions, 2015)
In the Chosŏn dynasty, intellectuals made conscious efforts to attain the ethics and ethical standards promoted by Neo-Confucianism. This was recognized as a requirement for a scholar to gain a position as a leader in society. Zhu Xi’s theory of kyŏngmul ch’iji 格物致知 (the investigation of things and the perfection of knowledge) suggested a method of internalizing morals through conscious effort, while Yi Hwang’s theory of lijado 理自到 (li approaches by itself) elaborately explained the moment of mastery. These theories also offer guidelines for distinguishing the moments prior to and immediately after mastery. The experience of internalizing ethics means the moment when the division between the mind and moral norms—the boundary between inside and outside of the body—is removed, and the mind of the individual extends beyond the body and experiences unity with universal ethics. Li 理 in Neo-Confucianism is what a person acquires and internalizes as universal norms and principles. One who has internalized li as their own set of ethics establishes Neo-Confucian ethics as a guideline for their behavioral decisions. Interpretations of ethics by political groups or schools of theory in which a person is involved function as a mirror reference point for assessing behavioral decisions. Accepting a theoretical school or political group’s perspective on ethics represents high reliance on and active acceptance and continuous consultation of the ethical standards and system created, diagnosed, and reconstructed by the school or group. In this case, it means that the individual’s mind extends to universal norms and principles through the interpretations of scholarly and political groups.